1916, the Irish rebellion [videorecording (DVD)] - Nic Dhiarmada, Bríona (PBS Distribution, 2016)
On Easter Monday 1916, a small group of Irish rebels took on the might of the British Empire. Although defeated militarily, the men and women of the Easter Rising would soon win a moral victory, with their actions leading to the creation of an independent Irish State and contributing to the eventual disintegration of the British Empire. They have inspired countless freedom struggles throughout the world.